Ultrasound-Guided Unilateral Posterior TAP Block for Lower Abdominal Surgery in Children (Central Asian Journal of Medical Sciences, 2021)
Objectives: This study aimed to evaluate the analgesic effect of ultrasound-guided transversus abdominis plane block in children. Methods: Children between 3-18 years of age on whom lower abdominal surgeries were preformed are included in this random control trial (RCT). The parents signed a written consent form. Patients were randomized into control and study groups. Every group was divided into subgroups either with or without inflammation. Results: There were no differences between the two studied groups regarding demographic and clinical characteristics. Hemodynamics were more stable in the study group than in the control group. After induction, BP decreased in all groups and increased after surgical incision except for the transversus abdominis plane elective (TAP + Elec) group. An elevated white blood cell count was used as the mean indicator of inflammation. The opioid usage during the operation was significantly different in the subgroups (p = 0.000). The relationship between WBC and opioid usage was weak, positive, and statistically significant. Postoperative pain and pain medication requirements were lower in the TAP block group. Conclusion: Transversus abdominis plane block under ultrasound guidance is easy, safe, reliable, and adequate for analgesia in children. This method can decrease surgical and postoperative pain and analgesic requirements.